2020
DOI: 10.1002/jbm.a.36871
|View full text |Cite
|
Sign up to set email alerts
|

Production and evaluation of decellularized extracellular matrix hydrogel for cartilage regeneration derived from knee cartilage

Abstract: Cartilage tissue engineering is the interdisciplinary science that will help to improve cartilage afflictions, such as arthrosis, arthritis, or following joints traumatic injuries.In the present work, we developed an injectable hydrogel which derived from decellularized extracellular matrix of sheep cartilage. Successful decellularization was evaluated by measuring the DNA, glycosaminoglycans (GAG), collagen contents, and histological analyses. There was a minor difference in GAG and collagen contents among na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 27 publications
0
42
0
Order By: Relevance
“…We previously demonstrated that miR133-overexpressing MSCs reduced fibrosis in MI through inhibiting Snail 1, a master regulator of epithelial-to-mesenchymal transition (EMT), and induced fibrogenesis during developmental and disease processes 50 . Furthermore, some studies showed that a hydrogel derived from decellularized bone extracellular matrix enhanced osteogenesis and cartilage regeneration in dental pulp stem cells or BMSCs 51,52 . Unlike bone or cartilage, the heart is a specialized organ that undergoes involuntary contraction, pumping blood to the rest of the body.…”
Section: Antifibrotic Effect Of Mscsmentioning
confidence: 99%
“…We previously demonstrated that miR133-overexpressing MSCs reduced fibrosis in MI through inhibiting Snail 1, a master regulator of epithelial-to-mesenchymal transition (EMT), and induced fibrogenesis during developmental and disease processes 50 . Furthermore, some studies showed that a hydrogel derived from decellularized bone extracellular matrix enhanced osteogenesis and cartilage regeneration in dental pulp stem cells or BMSCs 51,52 . Unlike bone or cartilage, the heart is a specialized organ that undergoes involuntary contraction, pumping blood to the rest of the body.…”
Section: Antifibrotic Effect Of Mscsmentioning
confidence: 99%
“…Scaffolds are bioactive substrates that play vital role in tissue repair and regeneration since they could mimic components and structural perspectives of extracellular matrix (ECM) [1][2][3][4]. Scaffolds should not only possess suitable mechanical properties, but also need to imitate the structural aspects of natural ECM to create an ideal support for cell seeding, adhesion, proliferation as well as differentiation with least inflammatory and toxic reactions [1][2][3][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow mesenchymal stem cells (MSCs) were isolated from wistar rats according previously described protocol [ 27 ]. Briefly, the wistar rats aged 6–8 weeks were terminated by cervical dislocation and soaked in 70% (v/v) ethanol and then the animal was transferred to a new dish.…”
Section: Methodsmentioning
confidence: 99%